Relationship among Globalization, Terrorism, and Economic Growth in Pakistan - Ayesha Naz; Zubaria Andlib; Azra Nasir (NUST Journal of Social Sciences and Humanities)
The current study investigates the interconnection of globalization, terrorism, and economic growth in Pakistan over the period of 1972 to 2019. ARDL co- integration bound test is used to establish the relationship among these variables. Limited empirical evidence is available on terrorism and globalization, particularly with reference to Pakistan. The empirical evidence confirms the long-run association among globalization, terrorism, and economic growth. Growth in per capita GDP increases terrorism because higher economic growth is not evenly distributed in Pakistan, while globalization reduces terrorist activities. Globalization, particularly political integration with rest of the world provides technical and financial assistance to overcome terrorism in Pakistan. Moreover, there is unidirectional causality from GDP growth to terrorism and bidirectional causality between globalization and terrorism. However, no evidence of causality is found between globalization and economic growth. This indicates that Pakistan is unable to get economic benefit from globalization because of its internal structural issue.